2022
DOI: 10.1111/zsc.12560
|View full text |Cite
|
Sign up to set email alerts
|

Assessing phenovariant species pairs of moray eels: Hybridization, introgression, and morphology

Abstract: Phenovariant is a pair of populations or species with distinct phenotypes but little to no genetic divergence, which may have resulted from strong assortative mating, hybridization, or incomplete lineage sorting that changes in the phenotype have exceeded the genotype. Previous studies had mainly tackled this issue on small, colourful reef fishes, but little effort has been made to the barely seen and solitary taxa like the morays (family Muraenidae). In the present study, three species pairs of sympatric mora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…In addition, U. mactanensis had the fewest number of vertebrae, one less than that of A. insuetus and two less than that of Gymnomuraena fusca although the vertebral count of G. fusca can only be approximated (Figure 7c and Table 3). Considering the size discrepancy of examined specimens may lead to allometric bias in moray eels (Huang et al ., 2022), we also tested the correlations between the TL and the three abovementioned characters in U. mactanensis . Linear regressions demonstrated that these values are relatively constant as the eel grows ( R 2 < 0.01; Figure 7), greatly supporting the morphological differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, U. mactanensis had the fewest number of vertebrae, one less than that of A. insuetus and two less than that of Gymnomuraena fusca although the vertebral count of G. fusca can only be approximated (Figure 7c and Table 3). Considering the size discrepancy of examined specimens may lead to allometric bias in moray eels (Huang et al ., 2022), we also tested the correlations between the TL and the three abovementioned characters in U. mactanensis . Linear regressions demonstrated that these values are relatively constant as the eel grows ( R 2 < 0.01; Figure 7), greatly supporting the morphological differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Some practical cases have been published in moray eels, such as the resurrection of Gymnothorax mucifer from the synonym of G. kidako (Huang et al ., 2019), and a review and description of a new species of Strophidon McClelland, 1844 (Huang et al ., 2020). However, one must be cautious of the limitations when using only a single genetic marker, such as in cases of phenovariant species pairs and hybridization in which genetic variations are inconsistent with morphological divergences (Huang et al ., 2022; Smith et al ., 2019; Victor, 2015). It is therefore important to evaluate the intra‐specific variations in morphology while incorporating molecular analyses in taxonomic works.…”
Section: Discussionmentioning
confidence: 99%